Unusual Etiology of Chronic Posterior Leg Pain in a Running Athlete: Could It Be a Schwannoma? A Case Report and Review of the Literature - Naoufal Elghoul; Omar Zaddoug; Mohammed Tbouda; Mohammed Benchakroun; Abdeloihab Jaafar (Case Reports in Orthopedics)
Schwannomas represent only 5% of all soft tissue tumors. As a variant of this tumor, the plexiform schwannoma is rare accounting for less than 5% of all schwannomas. Herein, we report a rare case of a 49-year-old athlete who suffered from a pain in the posterior aspect of the right leg one year before his presentation. Initially, a radiograph of his right leg showed no abnormality, and so, the emergency physician discharged him on analgesics and anti-inflammatory medications, and rest was advised. The persistent pain obliged the patient to consult our orthopedic department. On examination, we found a firm mass in the proximal medial aspect of his right leg. The neurovascular exam was normal. Sonography of the leg was not conclusive. Therefore, magnetic resonance imaging was performed, and a hemangioma or schwannoma was suspected. The patient underwent surgery in which the entire tumor mass was shelled out in one piece with no damage. The histopathological finding was concomitant with a plexiform schwannoma. Follow-up evaluation, sixteen months later, showed no evidence of recurrence, and the patient has regained his previous level of sportive activities. So, given the case described here, despite the rarity of the schwannoma, it should be taken into consideration as a possible diagnosis in such situation to promote early diagnosis and appropriate treatment.